ChemInform Abstract: Rh(III)‐Catalyzed Oxidative Annulation Leading to Substituted Indolizines by Cleavage of C(sp2)—H/C(sp3)—H Bonds. Issue 44 (13th October 2016) - Shen, Bingxue; Li, Bin; Wang, Baiquan
Abstract: The annulation reaction of pyridinium salts with alkynes tolerates a wide range of substituents in both partners providing highly functionalized indolizidines.